2014
DOI: 10.1519/jsc.0b013e318295644b
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Strength Training Effects on Change-of-Direction Sprint Performance

Abstract: The requirement profiles for sports such as soccer, football, tennis, and rugby demonstrate the importance of strength and speed-strength abilities, in addition to other conditional characteristics. During a game, the athletes complete a large number of strength and speed-strength actions. In addition to the linear sprints, athletes perform sprints while changing the direction (change-of-direction sprint [COD]). Therefore, this study aims to clarify the extent to which there is a strength training intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 21 publications
9
85
1
4
Order By: Relevance
“…On the other hand, negra et al (18) found significant correlation between lJ and two different agility tests in a large group of participants. The results of the present study showed that CODv of the young fencers correlated with almost all leg power parameters (explosive strength, horizontal jumps, speed and reaction jump test) while sJ was the best CODv performance predictor confirming the findings by others (11,18,22).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, negra et al (18) found significant correlation between lJ and two different agility tests in a large group of participants. The results of the present study showed that CODv of the young fencers correlated with almost all leg power parameters (explosive strength, horizontal jumps, speed and reaction jump test) while sJ was the best CODv performance predictor confirming the findings by others (11,18,22).…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, CODv tests seem to be associated with muscle strength of the participants, movement mechanics, exit velocity and increased elastic energy utilization during the eccentric phase of braking (11,22). On the other hand, negra et al (18) found significant correlation between lJ and two different agility tests in a large group of participants.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a previous study reported significant improvements in sprint times and change of direction in the T test following 8 weeks of squat jump training with 30 and 80% of 1RM (20). It has also been reported that strength training with either the front squat or BS over a period of 2 years significantly improves CODS performance of CODS in junior footballer players (17).…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, Comfort et al (8) reported concomitant improvements in BS strength and sprint performance over 5 and 10 m, following 8 weeks of resistance training in professional rugby league players. One study has also suggested that long-term strength training with the BS or front squat may improve change of direction performance in junior footballers (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although not universally confirmed, there is evidence of associations between the measures of maximal (1RM) [44] and relative strength (1RM/BM) [45], as well as between certain muscle mechanical properties, such as peak torque [46,47] and PP [39], and the ability of soccer players to perform complex multi-joint dynamic movements, e.g., jumping and sprinting actions. Independently of a player’s level, strength-related interventions represent a powerful training stimulus by promoting adaptations in a wide range of athletic skills (e.g., jumping, Table 1, Figures 1, 2 and 3 and Additional file 1: Figure S1-5) [2,3,6,8,10,12,14,15,19,21-23,48] and soccer-specific skills (soccer kick) [21,28] (Tables 1 and 2).…”
Section: General Physiological Considerations Of Strength/power Trainingmentioning
confidence: 99%